Identifying Factors Influencing Medium Density Fiberboard Production from Young Eucalyptus grandis, E. amplifolia, Corymbia torelliana and Cottonwood - Rockwood, Donald L.; Winandy, Jerrold E.; Gribbins, Neil R. (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
The primary objective of this study was to evaluate and compare the broad suitability of young Eucalyptus grandis W. Hill ex Maiden (EG), E. amplifolia Naudin (EA), Corymbia torelliana (F. Muell.) K.D.Hill & L.A.S. Johnson (CT), and Populus deltoides W. Bartram ex Marshall (PD) for making MDF by evaluating the basic wood properties of MDF produced from defibrillated Short Rotation Woody Crops (SRWC). Fast-growing EG, EA, CT, and PD may be deployed in SRWC systems in the lower Southeastern USA, especially in Florida. To evaluate these species for possible use as medium density fiberboard (MDF) and other composites, 2.5 m logs of three EG clones, three PD clones, six EA progenies, four CT trees, and one P. tremuloides Michx. (PT) tree from northern Wisconsin as a control were characterized for basic wood properties before being chipped, pulped, and pressed into MDF. The chips were thermomechanically pulped (TMP) for a two-phase study of the factors expected to influence suitability for MDF production: wood characteristics, refining system, resin system, and MDF formation. Phase I used TMP and 4% phenol-formaldehyde (PF) resin to produce 17 MDF species/genotype batches (S/GB). Thickness Swell (TS), Water Absorption (WA), Internal Bonding (IB), Modulus of Elasticity (MOE), and Modulus of Rupture (MOR) were evaluated to: 1) assess within species and within tree variation, 2) relate basic wood properties to MDF potential, and 3) examine repeatability of MDF-making. There was considerable variation among and within species, but only minor variation within individual trees. The analyses also examined the effects of species, genotype, and/or log on MDF panel properties, with a significance level of 5%. Species and S/GB means were tested using Duncan’s multiple-range test. Six of the 17 S/GBs had superior physical and mechanical MDF properties. In Phase II, two of the six better-performing Phase I S/GBs were evaluated, along with three average Phase I S/GBs. Phase II compared the effects on IB from using tube and drum blenders for resin application, the influence of using unscreened versus screened fibers, and the differences between using PF resin at 4% or 6% versus urea-formaldehyde (UF) resin at 8% or 12%. Overall, genetic variation among species, and particularly within these species, affected their potential for commercial MDF. Log specific gravity (SG), fines, MDF SG, and fiber length influenced MDF properties, as did refining and MDF-processing variables. Further study of specific processing requirements can optimize the potential of young EG, EA, PD, and CT genotypes grown as SRWCs for MDF and many other wood composites. These results are encouraging for the development and use of wood composites from SRWCs in Florida, the southeastern USA, and elsewhere.